AUTOMATED DISINFECTANT AGAINST THE SARS COV 2 VIRUS - Vanessa Ruiz Diaz de Salvioni, Viviana; Armoa, Alcides; Sosa Benítez, Claudelino; Armando Cantero Lesme, Lidio (Journal of Interdisciplinary Debates, 2023)
The objective of the research work was to determine the most optimal design of a disinfection cabin that meets quality and safety standards for users at the Universidad Private del Este Sade Ciudad del Este period 2021, of the Computer Engineering career; In this investigation, a descriptive-explanatory type analysis was carried out, which allowed interpreting the facts that have arisen, through a field investigation, several students were surveyed, for which the data collection was carried out with a sample population of 20 people among students, obtaining the following results that 85% of the people surveyed expressed that if it is necessary to implement, there is a high level of satisfaction, therefore the implementation of the system is accepted, likewise, it will have a scope clearly for the educational institution because Its main objective is to provide greater security with the implement of the disinfection cabin.